Glycan‐Mediated, Ligand‐Controlled Click Chemistry for Drug‐Target Identification. Issue 2 (23rd December 2015) - Stöckmann, Henning; Marin, Violeta L.; Nimmer, Paul; Balut, Corina M.; Davidson, Donald J.; Richardson, Paul L.; Vasudevan, Anil
Abstract: Membrane‐bound proteins are important pharmaceutical drug targets, yet few strategies exist for the identification of small‐molecule‐targeted membrane proteins in live‐cell systems. By exploiting metabolic glycan engineering of cell membrane proteins, we have developed an in situ glycan‐mediated ligand‐controlled click ("GLiCo‐Click") chemistry methodology that enables the attachment of small‐molecule chemical probes to their receptor protein through glycans on live cells. In addition to enabling receptor enrichment from cell lysates, this strategy can be used to demonstrate target receptor engagement and enables the molecular characterization of receptors. Abstract : GLiCo Click : We demonstrate a chemical biology strategy for efficient membrane protein crosslinking with a chemical probe that enables receptor visualization with fluorescence microscopy, receptor isolation, and glycan site mapping through nanoscale liquid chromatography coupled tandem mass spectrometry.